Pengaruh Marketing Mix Terhadap Keputusan Pembeli Motor Yamaha Pada PT. Hasjrat Abadi Manado - Tjahyadi, Zifora Rilifta; Sumayku, Sontje; Tumbel, Tinneke M (Sam Ratulangi University, 2017)
The purpose of this research is to find out the influence of marketing mix to the decisionof buyer of Yamaha motor at PT. Hasjrat Abadi Manado. The influence of the rapiddevelopment of the era makes every company should always do research anddevelopment to always be on a comfortable track. Seeing this, companies need to createbreakthroughs and strategic innovations in order to continue to increase revenue andprofits both quantitatively and qualitatively. PT. Hasjrat Abadi is the exclusivedistributor of Toyota and Yamaha vehicles in eleven leading provinces, parts of centraland eastern Indonesia. Tight competition is mainly happening on Yamaha and Hondafor the top spot. Yamaha motorcycle sales growth in December increased compared toHonda. Therefore, researchers who are interested in taking the title of the research are: